Unmasking of a second atrioventricular accessory connection by adenosine in a child with a long RP′ reentrant tachycardia. Issue 8 (August 1992) - Wienecke, Matthew M; Case, Christopher L; Gillette, Paul C
Abstract : A second unidirectional, retrograde accessory atrioventricular pathway was unmasked by adenosine during the intracardiac evaluation of a child with a reentrant long RP′ tachycardia. This case is further evidence of the value of adenosine during the evaluation of these types of tachycardias.